Contemporary European politics a comparative perspective - Magstadt, Thomas M. (Thomson/Wadsworth, 2007)
With coverage of ideology, political culture, and social constructs of regions and countries, this book helps you comprehend the changing global order and the challenges that the United States can face in the years ahead. It includes case studies that allow you to see how theory and concepts play out in real scenarios.